Determine the most appropriate period of time to monitor their blood lactic acid after the effort of 400 meters for juniors - Awad, Ali (Journal of Physical Education, 2014)
When measuring this lactic acid to evaluate the training load and to know the intensity of it. Sources showed that there is a physiological difference in the time of its concentration in the blood to take a sample of it to show the percentage of focus. Given the importance of the index of lactic acid in training, the importance of research appear in determining the most appropriate period of time to according to the times multiple is (3, 5, 7 and 10) minutes, to monitor the concentration of lactic acid in the blood after the effort competition to run 400 meters during the specific preparation stage for junior. The problem with research in the length of time in the concentration of lactic acid, which set up is multiple and whichever is the most appropriate is unknown therefore You must select a period of time suitable for monitoring the concentration of lactic acid in the blood during the three months of the specific preparation for the run 400 meters, either in terms of the sample is consist of (5) players . And used the statistical bag (spss) for the extraction test results and The researcher reached to the highest concentration that appeared in the fifth minute and the concentration of lactic acid in blood increases during the progress of the training process.